Pengaruh Knowledge Sharing, Perilaku Inovasi dan Kepuasan Kerja terhadap Kinerja Pegawai Bappeda Kabupaten Badung - Putra, I Made Joni Dwi; Utari, Nyoman Diah; Wirata, Gede (Jurnal Ilmiah Global Education, 2024)
Improving employee performance is crucial in achieving organizational effectiveness and efficiency. The Bappeda of Badung Regency plays a strategic role in regional planning and development, thus requiring optimal employee performance. This study aims to examine the influence of knowledge sharing, innovative behavior, and job satisfaction on employee performance at the Bappeda of Badung Regency. This research uses a quantitative approach, data collection using questionnaires, and multiple linear regression analysis. The research population is all employees of the Bappeda of Badung Regency, with a sample of 62 employees selected using the total sampling method. The results show that knowledge sharing, innovative behavior, and job satisfaction have a positive and significant influence on employee performance. The job satisfaction variable has a dominant influence compared to other variables. This research has important implications for the Bappeda of Badung Regency in improving employee performance. The recommendations given include building an effective knowledge sharing system, cultivating innovative behavior, and increasing employee satisfaction